Bimodal phase separated block copolymer/homopolymer blends self-assembly for hierarchical porous metal nanomesh electrodes. Issue 1 (6th December 2017) - Kim, Ju Young; Jin, Hyeong Min; Jeong, Seong-Jun; Chang, Taeyong; Kim, Bong Hoon; Cha, Seung Keun; Kim, Jun Soo; Shin, Dong Ok; Choi, Jin Young; Kim, Jang Hwan; Yang, Geon Gug; Jeon, Suwan; et al.
Abstract : Bimodal macro- and micro-phase separation of block copolymer/homopolymer blends for multiscale porous nanostructures. Abstract : Transparent conducting electrodes (TCEs) are essential components in various optoelectronic devices. Nanostructured metallic thin film is one of the promising candidates to complement current metal oxide films, such as ITO, where high cost rare earth elements have been a longstanding issue. Herein, we present that multiscale porous metal nanomesh thin films prepared by bimodal self-assembly of block copolymer (BCP)/homopolymer blends may offer a new opportunity for TCE. This hierarchical concurrent self-assembly consists of macrophase separation between BCP and homopolymer as well as microphase separation of BCP, and thus provides a straightforward spontaneous production of a highly porous multiscale pattern over an arbitrary large area. Employing a conventional pattern transfer process, we successfully demonstrated a multiscale highly porous metallic thin film with reasonable optical transparency, electro-conductance, and large-area uniformity, taking advantage of low loss light penetration through microscale pores and significant suppression of light reflection at the nanoporous structures. This well-defined controllable bimodal self-assembly can offer valuable opportunities for many different applications, including optoelectronics, energy harvesting, and membranes.